Overview of Motor Function in Non-Hemorrhagic Stroke Patients at Santa Elisabeth Hospital Medan Year 2024 - Lilis Novitarum; Vina Yolanda Sari Sigalingging; Mardiati Barus; Bryan Alexander Barus (Sean Institute, 2025)
Motor function is a function consisting of two components of motor response to stimuli and motor coordination strength. The type of research in this study is descriptive with a quantitative research design, with a population of 34 respondents, the sampling technique in this study was purposive sampling. The instrument used was a motor function observation sheet. It was obtained that the majority of respondents were in the motor function with the TRACE category, namely 17 respondents (50%) motor function with the NORMAL category with a total of 13 respondents (38.2%), motor function with the POOR category, with a total of 3 respondents (8.8%), and the lowest was the respondent with the FAIR motor function category, namely 1 respondent (2.9%). Based on the research and data processing that has been carried out regarding Motor Function in Non-Hemorrhagic Stroke Patients at Santa Elisabeth Hospital Medan in 2024, totaling 34 respondents, it was concluded that Based on the research results obtained from 3-4 respondents regarding the Description of Superior and Inferior Dextra Motor Function in Non-Hemorrhagic Stroke Patients at Santa Elisabeth Hospital Medan in 2024, the majority of respondents were in the motor function with the TRACE category with no limb movements at all.